(untitled) (World Bulletin of Social Sciences, 2022)
This study aims to cultivate the values of a leader in the nation’s younger generation and to find out to what extent external values influence the culture in this nation? This research was deliberately conducted to be able to test whether the theory found corresponds to the reality in the field. This study uses the method of observation and socialization approach. The results showed that there was an increase in the ability of grade 4 students at SDN 1 Telaga in reviving leadership qualities. This means that education on the value of leadership is one of the things that really helps students to develop their psychological growth and development for the future.